Phantom narratives: architectural analogies of site specific memories - Mitchell, Wesley (School of Architecture, Planning and Geomatics, 2018)
The role of this report not only serves as an account of the work done in fulfilment of the Masters of Architecture (Professional) degree but also acts as a way for me to recognize and position myself within the physical context of the Cape Town. In addition to this, it offers me an opportunity through which I am able to formulate my theoretical position concerning what it might mean to practice architecture in the context of the city. If you were to lay the map of Cape Town out on a nondescript flat surface, you would be able to take a pen, and with one forceful movement draw a line that cuts from the summit of Devil's Peak to the crest of Signal Hill. If this line is to be taken as a literal cut in the surface of the surface, slicing open the Mother City then we can spread her wounds open to examine her shape, the layers of her complex story and build up. The now severed embrace of the Mother City is the setting for this year's Landscapes of the Cape Studio. A city flanked by sloping mounds of earth and rock on either side creates a section of a valley. By imposing the drawings of Patrick Geddes' Valley Section of Civilization1 onto the section of the City Bowl, a possible lens through which the development of the city can be understood is created by the relationship between the physical attributes of these two drawings. Through the inclusion of miners, hunters, woodsmen, shepherds and more, the development of civilization can be understood as a network of occupants who have their roots in the earth they walked on, each responding to the various specificities and complexities of the site, adding to the flow of growth and life. Through investigations into this new hybrid Valley Section, under the pretext of the shepherds, assigned to me as part of a group assignment, a site visit was conducted where we would adopt the persona of a shepherd in a contemporary context.